Preface - Cunha, Jácome (2017)
[Excerpt] We were pleased to welcome delegates to the 2018 IEEE Symposium on Visual Languages and Human Centric Computing, held in Lisbon, Portugal at the Universidade NOVA de Lisboa. The theme of 2018’s conference was Building Human-Adaptive Socio-Technical Systems. These kinds of systems incorporate humans as both developers of and intrinsic parts of the system. We invited three keynote speakers, two from academia and one from industry following this theme. The first, Jason Hong, is a Professor in the Human-Computer Interaction Institute at Carnegie Mellon University. His research focuses on human-computer interaction and privacy and security, a combination that is exposed in new ways in Socio-Technical Systems. His talk focused on understanding and building new tools that address developers’ issues with supporting privacy. The second keynote was given by Geraldine Fitzpatrick who is a Professor of Technology Design and Assessment and leads the Human Computer Interaction Group at TU Wien in Vienna, Austria. Her research explores the intersection of social and computer sciences. Her talk uses the domain of developing supportive technologies for aging people to expose issues around modelling behaviors for systems and the realities of living with those models. The final keynote, from industry, was given by Rodrigo Sousa Coutinho, the co-founder and Strategic Product Manager at OutSystems, a Portugal-based software firm which constructed a platform that transforms visual models into running enterprise-grade applications. His talk focused on the story of bringing their visual language to market, and highlighted how OutSystems collaborated with academia. [...]